analisa Willingness To Pay (WTP) Dan kebutuhan Air Bersih Di Kecamatan Rengat Kabupaten Indragiri Hulu - Aidillah Fitria; Siswanto Siswanto; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Water is a basic of human need. Hence, there is a need to identified to what exterd people may attent of water charges. However, water is considered as free good. Water services carried out by water entities (PDAM) in Indonesia. Put charges for delivery of water. Treating water for population in the urban area. Therefore, willingness to pay water service as well as their willingness to connect where investigated in this study. The result of this research view that social economic factors has influence the willingness to pay (wtp) are revenue and total of water usage. The average of willingness to pay (wtp) is Rp 5.377,00/m3 greater than current charges is Rp 3.086,60/m3. Besides of that, 77,2% of citizen of this area have willingness to connect to water supply. It is projected that water supply required to meet. For 2014 demand is 81,2 lt/sec and 2032 is 102,2 lt/sec. There is a need to extend water treatment plan capacity up to 102 lt/sec in 2032. Keywords: willingness to pay (wtp), charges, needs, water, Rengat